"Compliance of the Indian National Task Force guidelines for COVID-19 recommendation by Indian doctors – A survey". Issue 5 (September 2020) - Gangopadhyay, Kalyan Kumar; Sinha, Binayak; Ghosal, Samit
Abstract: Background and aims: As the Coronavirus disease 2019 (COVID-19) pandemic unravels rapidly, there is a glut of confusing and divergent scientific information emanating from differing sources, including the Indian National Task Force for COVID-19. Thus, a web-based survey was conducted to decipher the approach of Indian doctors to the various options for treatment of COVID-19. Methods: A web-based questionnaire among one lakh doctors across India through email and social media was circulated. After data quality and internal validation, 826 responses were included for analysis. Basic demographic and comparative analysis were performed using the Python3.8.2 software (Windows 10 64 bit, USA). Results: Amongst all the states of India most respondents hailed from the top ten affected states. Overall 76.15% of doctors would either prescribe or consider prescribing hydroxychloroquine (HCQ) as prophylaxis for health-care providers (HCP). Doctors with experience of managing COVID-19 were more likely to advocate use of HCQ as prophylaxis for HCP (χ2 = 4.357, P = 0.037). Intensivists were more likely to advocate HCQ as prophylaxis (χ2 = 14.588, P < 0.001) as well as for management of mild to moderate COVID-19 (χ2 = 3.91, P = 0.048). In COVID-19, 65.8% doctors overwhelmingly preferred using anti-viral agents in severe cases, continuing ACEi/ARB (60.9%), and routinely screening for COVID-19 as a pre-operative strategy (73.85%). Conclusions: Indian doctors are largely following the scientific guidance provided by Indian National Task Force for COVID-19 and would consider prescribing HCQ as prophylaxis for COVID-19. They would also consider using it in mild to moderate COVID-19. Highlights: 76% doctors would consider hydroxychloroquine as prophylaxis for healthcare providers against coronavirus disease19. 68.89% of doctors would give or consider giving corticosteroids in severe coronavirus disease 19 infection. 73.85% of doctors surveyed support testing for coronavirus disease 19 as a routine pre operative investigation. 60.9% of doctors would continue angiotensin converting enzyme inhibitor & angiotensin receptor blocker.